Malaria, Helminth Infections and Clinical Status Among HIV-Infected Pregnant Women - Olawunmi Rashidat Rabiu; Hannah Dada-Adegbola; Catherine Olufunke Falade; Olatunbosun Ganiyu Arinola; Alexander Bababunmi Odaibo; George Olusegun Ademowo (Global Health and Education Projects, Inc., 2021)
Background or Objectives: Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) is widespread in sub-Saharan Africa with similarity in geographical distribution of major pathogens of public health interest. The aim of this study was to assess the effect of malaria and helminths on CD4 count, hematocrit values and viral load among HIV-infected pregnant women. Methods: One hundred and ninety-seven HIV-infected pregnant women aged 18-45 years were recruited from a registered HIV clinic and questionnaires were administered for socio-demographic details. Screening for malaria parasites in blood was through microscopy while helminths were identified in stool using Kato-Katz method. Hematocrit levels were determined through centrifugation of blood collected in capillary tubes. At the time of recruitment, most recent CD4 count and viral load was obtained from the patients' case notes. Results: About three-quarters (73.6%) of the women had above primary school level of education while more than half (60.2%) were petty traders. The prevalence of malaria parasites in the blood samples was 24.9%, while 3% were infected with helminths. There was only a single case of malaria, helminths and HIV co-infection in the study group. Prevalence of anemia was 75.6% with eight cases (4.1%) of severe anemia. About 86.6% of the women with anemia had low CD4 count (Χ2= 8.801, p=0.032). The mean CD4 count was significantly lower among those with co-infection of malaria and HIV. Conclusion and Global Health Implications: Malaria or helminth infection among HIV-infected women lowers the CD4 count and increases the viral load with little changes in hematocrit values. Routine screening of HIV-infected women for probable multiple infections will aid in improving their overall health and well-being. Key words: • HIV • Co-infection • CD4 count • Anemia • Pregnancy • Malaria • Nigeria   Copyright © 2021 Rabiu et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.